2015
DOI: 10.1016/j.stem.2015.08.007
|View full text |Cite
|
Sign up to set email alerts
|

The Isl1/Ldb1 Complex Orchestrates Genome-wide Chromatin Organization to Instruct Differentiation of Multipotent Cardiac Progenitors

Abstract: SUMMARY Cardiac stem/progenitor cells hold great potential for regenerative therapies; however, the mechanisms regulating their expansion and differentiation remain insufficiently defined. Here we show that Ldb1 is a central regulator of genome organization in cardiac progenitor cells, which is crucial for cardiac lineage differentiation and heart development. We demonstrate that Ldb1 binds to the key regulator of cardiac progenitors, Isl1, and protects it from degradation. Furthermore, the Isl1/Ldb1 complex p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
81
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 80 publications
(88 citation statements)
references
References 44 publications
7
81
0
Order By: Relevance
“…S4). Ldb1 may therefore be required to maintain stability of Isl1 protein in retina, similar to observations made in cardiac progenitors (Caputo et al, 2015).…”
Section: Ldb2 Is Sufficient To Sustain the Rpc Pool And Müller Glia supporting
confidence: 60%
See 2 more Smart Citations
“…S4). Ldb1 may therefore be required to maintain stability of Isl1 protein in retina, similar to observations made in cardiac progenitors (Caputo et al, 2015).…”
Section: Ldb2 Is Sufficient To Sustain the Rpc Pool And Müller Glia supporting
confidence: 60%
“…S5). Ldb1 was already shown to function in stabilizing the Isl1 protein in cardiac progenitors, these results suggest a similar role in the retina (Caputo et al, 2015). In contrast to the loss of Isl1 protein seen in Ldb1/Ldb2-deficient retinas, Lhx2 was maintained in the mutant cells throughout most of embryogenesis and was reduced only close to birth (E18.5, Fig.…”
Section: Ldb1 and Ldb2 Are Obligatory Co-factors Of Lhx2 In Retinal Pmentioning
confidence: 56%
See 1 more Smart Citation
“…These proteins may compete with LMO2 for LDB1 binding (59). Importantly, it was recently shown that LDB1 protects the related LIM homeodomain factor ISL1 from degradation during cardiac development (66). ISL and LHX proteins, such as ISL2 and LHX9 identified in this work, have their own DNA-binding homeodomains that may confer additional target gene diversity to LDB1/SSBP, which may be important for leukemic cell growth.…”
Section: Layer Et Almentioning
confidence: 68%
“…work rules the activity of Isl1 (46,47), to which we added a decisive component. We demonstrated that Isl1 is repressed by hypoxia responses through HES1/HIF1α-dependent recruitment of SIRT1 to the Isl1 gene and by activation of Sirt1.…”
Section: Discussionmentioning
confidence: 99%